The Metaverse as Green Technology: Revolutionizing Responsible Tourism Practices in Star-rated Hotels - Bharadwaj, Anindita; Tiu, Dhirendra; Chaudhary, Hare Krishna (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
The Metaverse is poised to be the next disruptive green technology set to profoundly impact society in the forthcoming decades. This research explores the transformative impact of the metaverse on responsible tourism practices within star rated hotels, focusing on its potential to revolutionize sustainability efforts in the hospitality industry. Employing a PRISMA approach, the study evaluates the metaverse's influence on guest engagement, eco-friendly technologies, and overall environmental conservation. It aims to provide insights into how virtual experiences, coupled with green technology, can reshape luxury hospitality and promote responsible tourism behaviours. The research also conducted SWOT analysis associated with metaverse integration, emphasizing the need for a balanced adoption to ensure harmony between technological advancements and ecological preservation in star-rated hotels.
Keywords: Metaverse; Responsible tourism; Disruptive green technology; Responsible tourism practices